2020
DOI: 10.1108/ejm-10-2019-0772
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative threat: underperforming to distance the self from undesirable groups

Abstract: Purpose This study aims to introduce the concept of dissociative threat, which is the fear of being associated with an undesirable (dissociative) group as a result of demonstrating ability in a domain that is stereotypically linked to that group. Consumers experiencing dissociative threats use inability signaling as a self-presentational strategy in which they present themselves as lacking ability in the dissociative domain. Design/methodology/approach Five experimental studies were conducted to test whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…On the one hand, wanting to avoid signaling the identity of a dissociative group increases intergroup differentiation (Berger & Heath, 2008). For example, males are less likely to engage with products or behaviors that are seen as feminines, such as a steak labeled as “ladies cut” (White & Dahl, 2006) and ethical products (Pinna, 2020); they even intentionally underperform in sewing, a domain stereotypically linked to females (El Hazzouri et al, 2020). Therefore, people's belief about “how good a product is for me” would depart from “how good the product is for dissociative outgroup members.” As feeling good about a product usually serves as information to indicate how good the product is (for its target consumers) (Schwarz, 2011), to make a fair judgment, people are likely to adjust their judgment of a product targeting a dissociative group in an opposite direction as indicated by their feelings (Houghton et al, 1999).…”
Section: Research Framework and Hypothesesmentioning
confidence: 99%
“…On the one hand, wanting to avoid signaling the identity of a dissociative group increases intergroup differentiation (Berger & Heath, 2008). For example, males are less likely to engage with products or behaviors that are seen as feminines, such as a steak labeled as “ladies cut” (White & Dahl, 2006) and ethical products (Pinna, 2020); they even intentionally underperform in sewing, a domain stereotypically linked to females (El Hazzouri et al, 2020). Therefore, people's belief about “how good a product is for me” would depart from “how good the product is for dissociative outgroup members.” As feeling good about a product usually serves as information to indicate how good the product is (for its target consumers) (Schwarz, 2011), to make a fair judgment, people are likely to adjust their judgment of a product targeting a dissociative group in an opposite direction as indicated by their feelings (Houghton et al, 1999).…”
Section: Research Framework and Hypothesesmentioning
confidence: 99%
“…Our undertaking partially fills this gap through examining the effect of a stereotype threat on consumer outcomes . Our particular focus is different from previous stereotype threat empiricism that has mostly centered on consumers’ performance on cognitive tasks and coping strategies in response to a stereotype threat (EI Hazzouri et al , 2020; Rydell et al , 2010; Steele and Aronson, 1995; Wraga et al , 2006). We proposed and found that a stereotype threat triggered by one’s shopping experience in retail settings constrained consumers’ cognitive resources, which then increased their reliance on price to make quality inferences.…”
Section: Discussionmentioning
confidence: 97%
“…Stereotype threat has also been shown to increase consumers’ preference for in-group service providers (Lee et al , 2011). A stereotype threat has also been determined to affect consumers’ performance at tasks that require using products linked to dissociative groups adversely (EI Hazzouri et al , 2020). These studies, however, have neglected one of the most prevalent contexts for consumer decision making: product purchases in stores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation